Quantitative Comparison of Mast cells in Major Salivary Glands in Hypothyroid State - Nida Qasim Hayat,Shahnila Nadir,Ansa Rabia (Journal of Rawalpindi Medical College, 2015)
Background: This experimental study was carried out to compare the number of mast cells in major salivary glands of albino rat in hypothyroid state. Methods: An experimental study was carried out on twenty male albino rats, weighing between 130-150 grams. The rats were divided into two groups; control group (A) and an experimental group (B), with 10 animals in each group. Hypothyroid condition was modeled in albino rats of experimental group (B) by giving them 0.02% w/v Methimazole (MMI) for three weeks in drinking water. After 4-weeks animals from both the groups were euthanized with chloroform. The blood sample was taken from each rat for determination of thyroid hormone concentrations in the serum by cardiac puncture. Serum T3, T4 and TSH levels were determined by enzyme immunoassay to confirm hypothyroid state of the animal. Major salivary glands; parotid, submandibular and sublingual were dissected and removed from the body. They were fixed in Bouin’s solution. Glands were further processed for light microscopy and for histological analysis of mast cells Toluidine blue stain was used. Counting of mast cells (MCs) was performed by superimposing the ocular graticule on the salivary gland preparation. Results: Statistically significant difference was observed between the MCs of parotid gland in group A (2.25±1.34/mm2) and B (3.70+1.11/mm2), p<0.017. No significant difference was observed in the mean number of MCs in the sublingual and submandibular salivary glands with p=0.511 and p=0.187 respectively. Conclusion: In hypothyroid state, there is significant difference in the number of MCs in the parotid glands and there is no significant difference in the number of MCs of submandibular and sublingual glands.